Asymmetrically structured polyvinylidene fluoride composite for directional high absorbed electromagnetic interference shielding. Issue 3 (15th November 2022) - Wu, Bozhen; Liu, Renrong; Yang, Yuhao; Zhu, Honghao; Yu, Yujing; Huang, Jiang; Li, Yulin
Abstract: In the face of electromagnetic pollution issues caused by the advancement of communication technology, it is of great significance to develop materials with high electromagnetic interference (EMI) shielding capability as well as high absorption efficiency. The nickel‐coated silicon carbide whiskers (Ni@SiCw)/graphene nanosheets (GNP)/polyvinylidene fluoride (PVDF) EMI shielding composites with the asymmetric structure are constructed by simple solution mixing and multiple hot pressing. Specifically, the Ni@SiCw in the top layer is prepared by simple electroless plating, and the saturation magnetization intensity reaches 12.50 emu/g. The combination of dielectric and magnetic losses provides reliable electromagnetic wave absorption performance with a reflection coefficient less than 0.35. GNP is selectively enriched in the bottom layer with a maximum conductivity of 85.43 S/m. The composite shows an EMI shielding performance of 36.83 dB when the GNP content is just 4 wt%, which means 99.98% of microwaves can be shielded. Furthermore, due to the distinct structure, the composites display various shielding mechanisms when electromagnetic waves are incident from different faces. Without a doubt, this asymmetric structure offers a novel approach to the preparation of directional EMI shielding materials. Abstract : An electromagnetic shielding composite with asymmetric structure was prepared in this study. The combination of magnetic loss, dielectric loss and conduction loss provides the composite an electromagnetic shielding performance of 36.83 dB with an absorption coefficient of 0.72.